Architect of death at Auschwitz : a biography of Rudolf Höss - Primomo, John W. 1952- (McFarland & Company, Inc., Publishers, 2020)
Escape and Capture -- Early Years -- The SS -- Creation of Auschwitz -- The Code of Barbarism -- Entrance Into Hell -- Life Within the Wire -- Crystal Death -- Property, Corruption and the Inspectorate -- Justice -- Responsibility and Atonement -- Execution.